SPE Annual Technical Conference and Exhibition 1988
DOI: 10.2118/18175-ms
|View full text |Cite
|
Sign up to set email alerts
|

Single-Phase Flow Through Natural Fractures

Abstract: OOPY%@t lW. sOOiOfY of Petroleum Engineers l%&I&MI&ww&w~5~&aonta!bn at tfre 6Srd Annual Tachnkel CeMarenca and Ex5ibltkm of tha SocIaty of Patroleum Englnaara hold in e, -,. LasmAczIt is well known that for q single-phasefluid flowing beteeen smooth parsllelplates, the pressure drop is proportional to the cube of the aperture septrathg the plates. Some .investig8tors2 vS have looked qt the qffect of surface rougbmesson flow ueing fabricatedsurfaces, inducedfractures, or sawed $urfaces and have found deviation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…This finding was in general accord with that reported in Ref. [2] and will be returned to subsequently.…”
Section: Fluid Frictionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding was in general accord with that reported in Ref. [2] and will be returned to subsequently.…”
Section: Fluid Frictionsupporting
confidence: 92%
“…Jones et al. 2 looks at laminar flow through rough natural fractures as occur in rock. Here a dependence of friction factor on roughness is observed and with λ ‐values of some 100 recorded.…”
Section: Fluid Frictionmentioning
confidence: 99%
“… Evans and Evans [1988] showed that the presence of immobile or low mobile liquid saturation in a simulated hydraulic fracture could enhance the nonlinear flow. For liquid flows, especially in fractures near wellbores, the nonlinear effects could be significant [ Guppy , 1987; Morris et al , 1987; Jones et al , 1988; Jung , 1989].…”
Section: Discrete Fracture Studiesmentioning
confidence: 99%
“…In naturally fractured reservoirs, the fluid enters to the well through the discrete open fractures intersected by the wellbore. Fluid flow through individual (discrete) fractures has been studied experimentally by Jones et al 2 whose conclusions were that the roughness of fractures play an important role causing turbulence and additional pressure drop. The smaller the fracture apertures the higher the roughness influence on turbulence effects.…”
Section: Introductionmentioning
confidence: 99%